Global analysis of benthic complexity in shallow coral reefs. (1st February 2023) - Li, Jiwei; Asner, Gregory P
Abstract: Three-dimensional shallow benthic complexity (also known as benthic rugosity) reflects the physical conditions of shallow coral reefs environments and can be used to estimate fish biomass and coral cover on reefs. Spatially explicit data on benthic complexity could offer critical information for coral reef conservation and management. However, benthic complexity has not yet been mapped at a global scale. We mapped global shallow water benthic complexity to 20 m depth at a spatial resolution of 10 m using 22 000 Sentinel-2 satellite images and a globally applicable underwater algorithm. We quantified geographic variation of benthic complexity in shallow coral reef areas from individual reef to ocean basin scales. We found that shallow benthic complexity is unevenly distributed worldwide, with high benthic complexity regions found in areas known to have high levels of benthic biodiversity such as the Coral Triangle, Coral Sea, and Great Barrier Reef. Yet nearly 60% of detected coral reef regions (size = 61 156 km 2 ) are not listed as protected under current marine protected plans. These unprotected regions include substantial reef areas of high benthic complexity that may harbor high levels of biodiversity. Our global coral reef benthic complexity map supports plans to improve marine protected areas, reef conservation, and management.